2001
DOI: 10.1002/ps.302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mutations in the two‐component histidine kinase gene that confer fludioxonil resistance and osmotic sensitivity in the os‐1 mutants of Neurospora crassa

Abstract: Osmotic-sensitive (os-1) mutant alleles in Neurospora crassa exhibit resistance to dicarboximides, aromatic hydrocarbons and phenylpyrroles. We have previously reported that the os-1 mutants can be classified into two groups based on their resistance to fungicides and osmotic stress: type I, which are highly resistant to iprodione and fludioxonil but moderately sensitive to osmotic stress, and type II, which are highly sensitive to osmotic stress but moderately resistant to fungicides. To explain the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
161
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 27 publications
12
161
1
Order By: Relevance
“…Further analysis showed that the os-1 mutant did not produce viable ascospores 10 d postfertilization (data not shown). The Y256M209 os-1 mutant allele was generated using UV light and contains a frameshift mutation at amino acid 294 (Ochiai et al, 2001). The difference in phenotypes observed for ⌬rrg-1 and os-2 versus os-1 mutants supports the hypothesis that the OS-2 MAPK pathway is regulated by multiple histidine kinases under different environmental conditions (e.g., osmotic stress vs. nitrogen starvation) in Neurospora.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Further analysis showed that the os-1 mutant did not produce viable ascospores 10 d postfertilization (data not shown). The Y256M209 os-1 mutant allele was generated using UV light and contains a frameshift mutation at amino acid 294 (Ochiai et al, 2001). The difference in phenotypes observed for ⌬rrg-1 and os-2 versus os-1 mutants supports the hypothesis that the OS-2 MAPK pathway is regulated by multiple histidine kinases under different environmental conditions (e.g., osmotic stress vs. nitrogen starvation) in Neurospora.…”
mentioning
confidence: 65%
“…For example, macroconidia from ⌬rrg-1 mutants develop a deep orange pigment and lyse easily and ⌬rrg-1 strains grow poorly in high concentrations of NaCl, KCl, and sorbitol. We determined that ⌬rrg-1 mutants were resistant to certain fungicides, a characteristic also associated with os mutants (Fujimura et al, 2000a,b;Ochiai et al, 2001;Zhang et al, 2002). We uncovered evidence suggesting that RRG-1 is upstream of the OS-4/OS-5/OS-2 MAPK pathway, in that OS-2-phosphate levels were greatly reduced in ⌬rrg-1 mutants relative to wild type.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…NIK1 orthologs from filamentous fungi are directly linked with the resistance to few important fungicidal agents used in agriculture. Point mutations in different HAMP domain repeats in Nik1p or its orthologs from B. fuckeliana and C. heterostrophus could confer varying degrees of drug resistance and osmosensitivity to the host (17,27,41). Thus, the structural insights about the HAMP domain repeats will not only help to understand these interesting mutants but also will aid in developing novel fungicides in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis of HKs by reciprocal BLASTP searches in Fusarium genome sequences led to the identification of Fhk1 (FOXG_01684) orthologues both in F. verticillioides (hypothetical protein FVEG_08048) and F. graminearum (hypothetical protein FGSG_07118) (Nagygyörgy and Ádám, unpublished). HKs have five HAMP (histidine kinase, adenylate cyclase, methyl binding protein and phosphatase) repeats: mutations in these sequences are responsible for the increased osmosensitivity and fungicide resistance of N. crassa, C. heterostrophus, Alternaria brassicicola and Botrytis cinerea (Ochiai et al, 2001;Yoshimi et al, 2004;Motoyama et al, 2005;Viaud et al, 2006). Recent microarray analyses have further shown that the transcriptional response to fludioxonil depends on a Hog1 orthologue in A. nidulans.…”
Section: The Role Of Hog1 Mapk Signaling In Stress and Fungicide Tolementioning
confidence: 99%